2014
DOI: 10.1002/mabi.201300525
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere‐Based Intracellular Sensing of Caspase‐3/7 in Apoptotic Living Cells

Abstract: A novel multifunctional probe to monitor intracellular enzymatic activity in living cells is successfully developed. Their use as accurate intracellular sensors by conjugation of an internal control (that gives an extra feature to both evaluate cellular-uptake efficiency and track probes over time) is reported. In particular, a specific application of these multifunctional microspheres as sensors of caspase-3/7 to monitor apoptosis by flow cytometry is described. The preparation of these devices together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The main advantages of using nanoparticles rather than classical approaches are that: a) they are more stable than fluorophore in solution [15], b) the fluorescence signal does not decreases rapidly during the first 24 hours after labelling, then zeroth generation can be set up using cell sample from day 0 [23] and c) they can be used to track a broad range of cellular types without any cytotoxic effect allowing its application in many biological/biomedical research fields [18]. To the best of our knowledge, cell clone formation assay based on nanotechnology imaging technique by using Quantum dot, has been the only reported to date to study the proliferative features [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of using nanoparticles rather than classical approaches are that: a) they are more stable than fluorophore in solution [15], b) the fluorescence signal does not decreases rapidly during the first 24 hours after labelling, then zeroth generation can be set up using cell sample from day 0 [23] and c) they can be used to track a broad range of cellular types without any cytotoxic effect allowing its application in many biological/biomedical research fields [18]. To the best of our knowledge, cell clone formation assay based on nanotechnology imaging technique by using Quantum dot, has been the only reported to date to study the proliferative features [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent proteomic studies showed no key regulators of cell cycle were affected by the internalisation of these NPs, resulting in a parentprogeny transfer of the nanofection load. Furthermore, NPs are not exported from the cells because externalization-exocytosis rate is negligible, allowing long-term monitoring [14], and their intracellular localization has been proved [15]. These properties make NPs ideal to be used as cell proliferation devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) from a wide range of different organic and inorganic materials are used in different biological and medical applications, such as diagnostic, non-invasive imaging and drug delivery to mention just a few 2 3 4 5 . Therefore, Engineered Nanoparticles (eNPs) are increasing their relevance in various fields, including targeted drug and gene delivery systems, biosensors and cancer treatment 6 7 8 9 10 11 12 13 14 15 . In particular, polystyrene eNPs have an extensive use as systems for in vitro applications such as cell-sorting, labelling and cellular delivery 16 17 .…”
mentioning
confidence: 99%
“…Therefore, the hybridisation processes can take place in solution, which means that they are thermodynamically favourable when compared to solid-phase processes [ [17] , [18] , [19] ]. To achieve this, we used PS-NPs due to their robustness and stability in the biological environment, and their compatibility with standard multistep chemistries, allowing different orthogonal conjugation strategies [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. The novel PS-NPs used in this work are bifunctionalised containing both a streptavidin as the high-affinity partner of biotin, and a fluorophore (5(6)-carboxyfluorescein, -FAM-) as tracker.…”
Section: Introductionmentioning
confidence: 99%